HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN MORAL KERJA GURU DI SMK NEGERI 2 BUKITTINGGI - Fitria Halim (Jurnal Bahana Manajemen Pendidikan, 2014)
This research about leadership of headmaster and teacher morale, also to see the relationship between the two variables. Population are 70 teachers and 40 samples using proportional stratified random sampling technique. This research instrument is a questionnaire in the form of a Likert scale, a score of variable leadership of headmaster 0.907 and teacher morale 0.897 that  means instrument is reliable. Data were analyzed using product moment correlation, get rscore = 0.33 > = 0.284 believed rtabel standard 95%. Research has come to the conclusion the relationship between leadership of headmaster with the morale of teachers in SMK 2 Bukittinggi. Key word : Kepemimpinan Kepala Sekolah dan Moral Kerja Guru